2020
DOI: 10.1186/s12884-019-2704-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycated albumin in pregnancy: reference intervals establishment and its predictive value in adverse pregnancy outcomes

Abstract: Background: Many efforts have been focused on the alternative glycemic marker glycated albumin (GlyA) and its application in pregnancy during which profound physiological changes take place. Our objective was to determine the reference intervals (RIs) of GlyA in healthy Chinese pregnant women and to assess the predictive value of serum GlyA in adverse pregnancy outcomes. Methods: Totally 421 healthy subjects including 137 in the first trimester, 152 in the second trimester, and 132 in the third trimester were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(47 reference statements)
2
6
0
Order By: Relevance
“…However, matching for gestational age was performed to address gestational age as a confounder. Dong et al found that with increasing gestational age, maternal serum GA decreased in women with GD who were normoglycemic 20 . We found lower maternal GA levels among obese women and this is in keeping with Hiramatsu et al’s findings that maternal GA levels decreased more in obese women as the pregnancy progressed to the third trimester 21 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, matching for gestational age was performed to address gestational age as a confounder. Dong et al found that with increasing gestational age, maternal serum GA decreased in women with GD who were normoglycemic 20 . We found lower maternal GA levels among obese women and this is in keeping with Hiramatsu et al’s findings that maternal GA levels decreased more in obese women as the pregnancy progressed to the third trimester 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Dong et al found that with increasing gestational age, maternal serum GA decreased in women with GD who were normoglycemic. 20 We found lower maternal GA levels among obese women and this is in keeping with Hiramatsu et al's findings that maternal GA levels decreased more in obese women as the pregnancy progressed to the third trimester. 21 Their explanation for this was that albumin turnover may be increased in obese women because of their chronic low-grade inflammatory state.…”
supporting
confidence: 92%
“…Our study reaffirmed the findings of other investigators that BMI has an inverse relationship with %GAlb throughout gestation. 20,23 BMI did not decline to its early pregnancy state, reflecting weight retention in the PP period. The lack of PP weight loss may be partially responsible for the lack of return of %GAlb to nonpregnant levels, as higher BMI may have been correlated with lower %GAlb levels, but BMI did not completely explain the findings in adjusted models.…”
Section: Discussionmentioning
confidence: 84%
“…Others have examined the behavior of this biomarker during gestation to examine its role in gestational diabetes diagnosis, monitoring, and predicting neonatal outcomes 20,26,36 ; however, the PP period was not included in their analyses. While some investigators have proposed that % GAlb is useful in correlation with self-monitored postprandial glycemia among pregnancies affected by GDM, 23,37 these studies were restricted to those with GDM compared with controls and did not control for the effect of BMI on %GAlb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation